Online grocery shopping behavior during COVID-19 pandemic: An interdisciplinary explanation - Kharabela Rout; Priti Ranjan Sahoo; Archana Bhuyan; Arvind Tripathy; Smrutirekha (Cogent Business & Management, 2022)
The second wave of COVID-19 forced many countries to impose a strict lockdown to check the escalated infection rate. The imposed lockdown and social distancing made people involuntary home arrested, and people shifted back to virtual space by adopting, starting from work from home to online shopping. The essentials such as food and grocery shopping moved from brick-and-mortar stores to online stores. Consumers immensely adopted online grocery shopping to cope with the severity of the second wave of COVID-19. This study predicts consumers' online food and grocery buying behavior during a pandemic by considering the health threat-related and perceptual factors that got neglected in the extant literature. The current study adopted Protection Motivation Theory (PMT) and Technology Acceptance Model (TAM) as a theoretical lens to explain the online grocery buying intention of Indian consumers in the COVID-19 pandemic scenario. Data was gathered from 133 online grocery consumers and were analyzed using Smart-PLS 3 to examine the proposed model. The study revealed that factors, namely self-isolation intention, perceived ease of use, perceived usefulness, and customer perceived value, have positively and significantly predicted the online grocery shopping intention. Further, the perceived usefulness and self-isolation intention positively and greatly influence the customer perceived value. A small sample is noted as the prime limitation of the study. Managerial and theoretical implications are suggested in this study.
Keywords: 650; perceived usefulness; consumer-perceived value; isolation intention; online grocery shopping; perceived ease of use